Composition of fatty acids in the muscle and fat tissue of young sheep - O. N. Orlova; L. S. Dmitrieva; V. I. Erochenko; L. V. Krichun (Пищевые системы)
The article presents the results of studies of the content of fatty acids in the lipids of the muscle tissue of young rams, and the composition of fatty acid of the internal fat of young rams, obtained from purebred genotypes (Soviet merino) and crossbred sheep genotypes: Soviet merino x Dzhalginsky merino and Soviet merino x Stavropol variety. Sheep were raised by moderate fattening. For the purposes of research the control group of sheep was slaughtered at the age of 8 months. As a result of analyzing the composition of fatty acid in the samples of muscle tissue and internal fat of the considered animals, 13 and 11 fatty acids, respectively, were identified. The lipids of muscle tissue showed an increased share of saturated fatty acids (53.93–56.34%) in reference to the total composition of fatty acids. In all studied groups, the internal fat of young rams contained a large amount of saturated fatty acids: from 64.46 (purebred) to 67.71% (crossbred). The calculated atherogenicity indices of muscle tissue (IA = 0.99–1.18) and fat tissue (IA = 1.11–1.21) in all groups of animals were at a low level; thrombogenicity indices of muscle tissue (IT = 1.98–2.28) and fat tissue (IT = 2.97–3.71) proved to be higher.